Development of an APPLE-III undulator for FLASH-2. Issue 1 (1st December 2022) - Tischer, M; Bienert, H; Götze, K; Meissner, D; Neumann, P; N'Gotta, P; Ramm, T; Schöps, A; Talkovski, P; Telawane, S; Vagin, P
Abstract: The use of circularly polarized soft X-rays at the FLASH-FEL at DESY will be a very versatile tool for investigation of dynamic properties in nanomagnetism. For that purpose, the development of a variable polarization undulator was started to provide an afterburner downstream of the FLASH2 SASE undulators. It will serve to produce circularly polarized light with a wavelength of 1.33 nm to 1.77 nm (890 eV - 700 eV) to investigate the L-edges of Fe, Co, and Ni. This wavelength range together with the future maximum beam energy of 1.35 GeV at FLASH leaves only a small and ambitious parameter window for the undulator if a noteworthy tunability range shall be provided. We report on design and development of an APPLE-III undulator with 17.5 mm period length operating at a minimum magnetic gap of 8 mm which will make use of a magnetic force compensation scheme. A short prototype has been built to verify and iterate both the mechanical and magnetic concept. Details on the keeper design, results of the magnetic measurements and the tuning concept will be presented.